2015
DOI: 10.15184/aqy.2015.80
|View full text |Cite
|
Sign up to set email alerts
|

Northern outpost of the Caliphate: maintaining military forces in a hostile environment (the Dariali Gorge in the Central Caucasus in Georgia)

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…10). Although surface materials at the site were very sparse, the plan of the fortification walls conforms to plans common in the Sasanian period (Sauer et al 2015a(Sauer et al , 2015b. We identified a similar feature on CORONA imagery further north on the east bank of the river, that is likely also to be a fort given the presence of several parallel banks of rooms characteristic of Sasanian military barracks (Fig.…”
Section: Settlement Historysupporting
confidence: 65%
“…10). Although surface materials at the site were very sparse, the plan of the fortification walls conforms to plans common in the Sasanian period (Sauer et al 2015a(Sauer et al , 2015b. We identified a similar feature on CORONA imagery further north on the east bank of the river, that is likely also to be a fort given the presence of several parallel banks of rooms characteristic of Sasanian military barracks (Fig.…”
Section: Settlement Historysupporting
confidence: 65%
“…The domestic herbivores (sheep, goat and cattle) are dominant in the faunal remains. Very interestingly, specimens of Caucasian tur (Capra caucasica) were also found among the remains (49,50). Good preservation allowed paleogenetic analysis of several species in this site.…”
Section: Dariali Tamara Fort Georgiamentioning
confidence: 95%
“…A final PCR amplification step followed the enrichment with 16 cycles. Captured mitochondrial sequences were then sequenced on an Illumina® MiSeq at TrinSeq (50 (147,148) are shown in Fig. S6.…”
Section: Mitochondrial Capturementioning
confidence: 99%
“…P'arnavaz' bride is described only as being from Durżuket'i, and is not considered to be Alan-a point that is clear since the source distinguishes between the Durżuk kinsmen of Saurmag's mother and the Alan kinsmen of Saurmag's father. 28 The ancient North Caucasus was clearly 26 Archaeological research at both of the major passes in recent years has demonstrated abundant investment in Late Antiquity, but little for earlier periods, although this picture may change with further research: Gadžiev 2008;Sauer et al 2015;Lawrence -Wilkinson 2017. 27 Pliny, NH 6.18: nec in alia parte maior auctorum inconstantia... 28 P'arnavaz had married his sister to the king of the Alans: KC, ed.…”
Section: The People Of the Northmentioning
confidence: 99%